Influence of team identification on proactive work behavior and task performance: The mediating role of team support for innovation - Muhammad Shahid; Shoaib Aslam; Muhammad Sheeraz; Muhammad Bilal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study aims to investigate a model that applies team support for innovation as a mediating mechanism for the association of team identification (TI) with task performance (TP) and proactive work behavior (PWB) in the software companies. The sample encompasses 92 teams working in software companies in Pakistan. Data were collected from two sources: team identification, team support for innovation (TSI), and task performance data were collected from employees, while PWB data were collected from the team supervisor. Multi-level data was analyzed using structural equation modelling technique through Mplus, AMOS and SPSS software. Findings of the study revealed that team support for innovation plays an intervening role between team identification and its outcomes (PWB and TP). This study proposes that team support for innovation can effectively encourage PWB and TP. Therefore, managers and leaders of software companies who aim to achieve PWB and TP need to encourage team identification among the team members. The present paper links a gap relating to factors and antecedents that impact proactive work behavior and task performance in a multi-level research design.
Keywords: 330; Team support for innovation; team identification; proactive work behavior; task performance; software companies; Pakistan